STABILITE DES ELEMENTS DES STRUCTURES EN COMPOSITES PAR INTERPRETATION DE LA THEORIE DE LA SECURITE - PLUVINAGE, G; SAPUNOV, V.T (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
For different types of materials including composites, an approximate solution of table bending reduction factor slenderness is proposed. The lost of stability is considered as a failure of the criterion. The probability of failure is thencomputed for plates and bars in composite.